Measurement of the quasi free $np → npπ^+π^-$ and $np → ppπ^-π^0$ reactions at 1.25 GeV With HADES - HADES collaboration (105 authors) (2014)
We present the results of two-pion production in tagged quasi-free np collisions at a deutron incident beam energy of 1.25 GeV/c measured with the High-Acceptance Di-Electron Spectrometer (HADES) installed at GSI. The specific acceptance of HADES allowed for the first time to obtain high-precision data on pi^+pi^- and pi^-pi^0 production in np collisions in a region corresponding to large transverse momenta of the secondary particles. The obtained differential cross section data provide strong constraints on the production mechanisms and on the various baryon resonance contributions (DeltaDelta, N(1440), N(1520), Delta(1600)). The invariant mass and angular distributions from the np -> nppi^+pi ^-and np -> pppi^-pi^0 reactions are compared with different theoretical model predictions.